Internal Control of Trade Goods Supply at CV Syntek Auto Pekanbaru - Eddy, Pujiono; Diputra, Dharma Okta; Irman, Mimelientesa; Anton; Estu, Ahmad Zulkarnain (Interconnection: An Economic Perspective Horizon, 2023)
Inventory is one of the most important assets in a trading company. Keeping the inventory from the bad things that may happen then required good internal inventory control. Therefore, the purpose of this study is to determine the application of internal control inventory on the CV. Syntek Auto has been running effectively or not. The type of data used in this study is primary data and secondary data. Primary data is obtained through questionnaires. Secondary data obtained from scientific sources related to the problems studied. This research uses a descriptive analysis method and a sign test. From the result of the research, it is known that the internal control of merchandise inventory covering the control environment, risk interpretation, information and communication, and monitoring have been effective except for the control activities which have not been effective yet.